Diagnosis and Etiological Analysis of Gastroesophageal Reflux Disease by Gastric Filling Ultrasound and GerdQ Scale - Bo Wang (Hindawi Limited, 2021)
Objective. To investigate the diagnosis and etiological analysis of GERD by gastric filling ultrasound and GerdQ scale. Methods. The clinical data of 100 suspected GERD patients were selected for retrospective analysis. The selection time was from June 2016 to June 2019. According to the gold standard (endoscopy) results, they were divided into the gastroesophageal reflux group (positive, n = 62) and the nongastroesophageal reflux group (negative, n = 38); both gastric filling ultrasound and GerdQ scale examination were performed to compare the positive predictive value and negative predictive value, evaluate the abdominal esophageal length, His angle, and GerdQ scale score, and analyze the AUC value, sensitivity, specificity, and Youden index of His angle, length of abdominal esophagus, combined ultrasound parameters, and GerdQ scale in the diagnosis of GERD. Results. 100 patients with suspected GERD were diagnosed as GERD by endoscopy; in a total of 62 cases, the percentage was 62.00%. Among them, 28 cases were caused by the abnormal structure and function of the antireflux barrier, accounting for 45.16%, 18 cases were caused by the reduction of acid clearance of the esophagus, accounting for 29.03%, and 16 cases were caused by the weakening of the esophageal mucosal barrier, accounting for 25.81%. After ultrasound detection, the positive predictive value was 88.71% and the negative predictive value was 81.58%; after the GerdQ scale was tested, the positive predictive value was 71.43% and the negative predictive value was 54.05%. The length of the abdominal esophagus in the gastroesophageal reflux group was lower than that of the nongastroesophageal reflux group, while the scores of His angle and GerdQ scale were higher than those in the gastroesophageal reflux group (P<0.05). ROC curve analysis showed that the AUC values of His angle, length of abdominal esophagus, combined ultrasound parameters, and GerdQ scale to diagnose GERD were 0.957, 0.861, 0.996, and 0.931 (P<0.05), their sensitivity was 93.5%, 98.40%, 98.40%, and 90.30%, and the specificity was 92.10%, 63.20%, 100.00%, and 92.10%, respectively. Conclusion. Both gastric filling ultrasound and GerdQ scale have a certain application value in the diagnosis of GERD, but the former has a higher accuracy rate, and it is more common for gastroesophageal reflux caused by abnormal structure and function of antireflux barrier in etiological analysis.